2013
DOI: 10.1097/mao.0b013e31828bb567
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic and Systemic Steroids for Sudden Hearing Loss

Abstract: The addition of intratympanic steroids to the conventional systemic steroid therapy may provide a safe and potentially effective therapeutic option in patients with mild-to-severe ISSNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 22 publications
1
33
2
4
Order By: Relevance
“…Two studies [19,20] found that ITSI therapy was equivalent to systemic therapy in hearing level (HL) improvement, and one [21] found that combination therapy was similar to systemic steroids. Of the two studies [22,23] comparing systemic, ITSI and combination therapy, one found that combination therapy was superior to systemic treatment alone (87.5 vs 44.4 %).…”
Section: Resultsmentioning
confidence: 98%
“…Two studies [19,20] found that ITSI therapy was equivalent to systemic therapy in hearing level (HL) improvement, and one [21] found that combination therapy was similar to systemic steroids. Of the two studies [22,23] comparing systemic, ITSI and combination therapy, one found that combination therapy was superior to systemic treatment alone (87.5 vs 44.4 %).…”
Section: Resultsmentioning
confidence: 98%
“…However, the findings of the use of combination therapy in SSNHL have been inconsistent. Some studies found combination therapy promoted pure-tone average (PTA) improvement and a recovery rate similar to the use of systemic steroids alone [Arastou et al, 2013;Battaglia et al, 2008;Koltsidopoulos et al, 2013], and others have not [Lim et al, 2013]. A recent meta-analysis, which included eight studies, found that the combined therapy had better outcomes in PTA improvement and in recovery rate compared with systemic steroid use alone [Gao and Liu, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Battaglia et al [25] and Gundogan et al [29] reported better hearing improvement in ITS in combination with SS according to PTTA. On the other hand, Baysal et al [30] and Koltsidopoulos et al [31] concluded no superior hearing improvement of ITS in combination with SS.…”
Section: Discussionmentioning
confidence: 98%